The impact of nurse-led, AI-assisted perioperative health education on psychological status and quality of life in patients undergoing lung cancer surgery - Shen, Chenminghuang; Huang, Yuzhu; Wang, Bingbing; Ye, Xiaoyan; Jiang, Jinzhi (Frontiers in Psychology, 2025)
ObjectiveTo evaluate the clinical value of integrating artificial intelligence (AI) into perioperative health education for patients undergoing surgery for lung cancer.MethodsThis retrospective study included patients who underwent radical resection for non-small cell lung cancer (NSCLC) in the Department of Thoracic Surgery at the First Affiliated Hospital of Xiamen University between January and December 2024. According to the perioperative education method, patients who met the inclusion criteria from January to May 2024 were included in the conventional group, whereas those from June to December 2024 were included in the AI-assisted group. All patients received standardized rehabilitation education based on a unified handbook. On this basis, the AI-assisted group additionally received individualized health education and psychological counseling generated by AI, which was verified and supplemented by nurses. Clinical data and validated questionnaire scores were collected and analyzed.ResultsA total of 135 patients were included, with 70 in the conventional group and 65 in the AI-assisted group. There were no significant differences in demographic and clinical characteristics between the groups. Compared with the conventional group, patients in the AI-assisted group scored significantly higher on the “confrontation” dimension of the Medical Coping Modes Questionnaire (MCMQ), indicating a stronger tendency toward active coping, whereas no significant differences were observed in the “avoidance” and “acceptance–resignation” dimensions. Regarding psychological status, the AI-assisted group had significantly lower depression and anxiety scores postoperatively, while stress scores showed no significant difference. Quality of life, assessed by the World Health Organization Quality of Life-BREF (WHOQOL-BREF), revealed that the AI-assisted group had significantly higher scores in the psychological and social domains as well as the overall score, with no significant differences in the physical or environmental domains.ConclusionNurse-led perioperative health education supported by AI tools can help optimize patients' coping strategies, reduce negative psychological states, and improve quality of life after lung cancer surgery.